Penggunaan Pijat Refleksi untuk Mengurangi Nyeri pada Pasien Kanker Payudara - Hasni Hasni; Melty Melty; Kadek Ayu Erika; Mulhaeriah Mulhaeriah (Jurnal Keperawatan Silampari, 2022)
This study aims to review the effectiveness of reflexology on pain reduction in breast cancer patients. The research method used is writing a systematic review using search results of scientific publications published between 2016 and 2021 through international electronic databases such as PubMed, ProQuest, CINAHL, and Cochrane, which then follows PRISMA guidelines and research questions using PICO. The results showed that eight articles from the search contained six RCT articles and two cohort articles than in each piece provided the same intervention, namely reflexology intervention to reduce pain in breast cancer patients which later resulted in reduced pain felt by breast cancer patients. . In conclusion, all articles show the effectiveness of reflexology to reduce pain in breast cancer patients. Keywords: Breast Cancer, Pain, Reflexology